Culpabilização de mulheres vítimas de estupro: subtipos femininos e variáveis correlatas - Farias, Mariana Gonçalves (2019)
Blaming the victim consist of the imputation of guilt for the crime to the victim and occurs when individuals resort to characteristics or behaviors of the victim to blame her. This dissertation aimed to understand the attributions of blame to rape victims by analyzing observer' attributes (human values, right-wing authoritarianism, orientation to social dominance, ambivalent sexism, and acceptance of rape myths) and their interactions with female subtypes. The sample was composed of 391 individuals, mostly female (61.2%), heterosexual (76.7%), and Catholic (42.2%). Participants read a rape scenario that varied in terms of female subtype (traditional victim vs. non-traditional victim) and completed scales measuring human values, social dominance, right-wing authoritarianism, ambivalent sexism, and acceptance of rape myths. All ethical procedures were followed. Results revealed no significant differences between responses to the traditional victim vignette and the non-traditional victim vignette, regarding blame attributions. Greater victim-blaming was attributed by men vs. women, high vs. low right-wing authoritarianism, and high vs. low orientation to social dominance. Results indicated blame attributions were negatively correlated with interactive, excitement, and suprapersonal values. Right-wing authoritarianism did not predict rape myths acceptance. Therefore, it was excluded from the final model of blame attributions. The proposed model showed reasonable adjustment indexes. Despite some limitations, this dissertation advances by offering an integrative model for understanding the attribution of blame in rape cases.